State of the world 2015 : confronting hidden threats to sustainability - Gardner, Gary T., 1958-; Prugh, Tom; Renner, Michael, 1957- (State of the world ;, 2015)
We think we understand environmental damage: pollution, water scarcity, a warming world. But these problems are just the tip of the iceberg. Food insecurity, financial assets drained of value by environmental damage, and a rapid rise in diseases of animal origin are among the underreported consequences of an unsustainable global system. In "State of the World 2015," the flagship publication of The Worldwatch Institute, experts explore hidden threats to sustainability and how to address them. Eight key issues are addressed in depth, along with the central question of how we can develop resilience to these and other shocks. With the latest edition, the authorities at Worldwatch bring to light challenges we can no longer afford to ignore.